Analysis of growth mindset and grit in the academic achievement of junior high school students in Pesawaran regency - Putri Wulandari; Susanto Susanto; Juni Suryanadi (International Journal of Science and Applied Science: Conference Series, 2025)
Academic achievement is the main indicator used to assess the effectiveness of an education system. Until now, student success has often been measured based on cognitive abilities such as intelligence, memory, and logical thinking skills. Various studies have shown that internal non-cognitive factors, such as growth mindset and GRIT, also contribute significantly to students' academic achievement. Growth Mindset refers to the belief that intelligence and ability are not fixed, but can be developed through effort, perseverance, and continuous learning. Students with this mindset tend to be more open to challenges, less afraid of failure, and more enthusiastic about the learning process. Meanwhile, GRIT is a combination of perseverance and consistency of interest in the long term. Individuals with high levels of GRIT are able to maintain their enthusiasm and commitment to their goals, even when faced with various obstacles and failures. Initial observations conducted in several junior high schools in Pesawaran Regency revealed a number of problems related to students' non-cognitive aspects. Many students showed low self-confidence, gave up easily when encountering difficulties, and did not have consistent study habits. This study used a quantitative approach with correlational methods and multiple linear regression analysis. The data collection instrument was a questionnaire distributed to 33 respondents, which was then analyzed to see the relationship and influence between these variables. The results of the study show that a growth mindset contributes 75% to students' academic achievement, while GRIT contributes 51.8%. When these two variables are combined, the results show that both simultaneously have a significant influence on academic achievement.